Genetic diversity in matora goats and genetic management of conservation herds - Oliveira Moura, J.; Guimarães Campelo, J. E.; Bajay, M. M. [UNESP]; Lindenberg Rocha Sarmento, J.; Barros Britto, F.; Leal, T. M.; Silva Costa, M.; Helcias Cavalcante, D.; Figueiredo Carvalho, M. D.; Mello Araújo, A. (Cordoba University Press (UCOPress), 2019)
This study was aimed at assessing the genetic diversity in herds of Marota goats and examine the impact of molecular markers in the genetic management of conservation herds. Seventy-six animals of one conservation heard and ten animals of a private herd were genotyped with the Illumina 50K goat SNP Chip. The dispersion of animal was evaluated with a principal component analysis (PCA) and a dendogram. Matings were simulated between animals with the largest distance in the dendogram and lowest coefficient of inbreeding (FIS) (Mana-gement I) and compared to random mating (Management II). High values of observed (Ho) and expected (He) heterozygosity were obtained for adult animals (Ho=0.372 and He=0.405) and offspring (Ho=0.359 and He=0.374). The mean FIS was 6.4%, indicating a low risk of gene loss in the conservation herd. Genetic variability was also observed in the private herd (Ho=0.374 and He=0.498), but the risk of endogamy was higher. The PCA revealed that the two herds were genetically similar. The simulation of 10 mating pairs of each breeder indicated that the mean coefficient of inbreeding of the formed pairs in Management I was statistically lower than that of the Management II. Thus, there is genetic variability in the herds examined, but with with signs of consanguinity. Also, in small herds in which replacement is carried out with animals within the herd, matings based on genetic criteria is an option to control inbreeding.
Diversidade genética em caprino marota e manejo genético para rebanhos de conservação
Keywords: Genetic resources; Microarray; Risk of extinction; SNP